STUDY OF MORPHOSTRUCTURE OF EARTH CRUST SEDIMENTARY LAYER ON NORTHERN FOLDED ZONE OF ARMENIA BY MORPHOMETRIC DATA (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The application of new methodological approachеs in using morphometric methods and allocation of morphostructure of the Earth Crust sedimentary layer on Northern folded zone of Armenia and its geological interpretation are considered.
Keywords: morphometric method; antiklinal and Horst structures; Earth Crust sedimentary layer; morphostructures